Abiotic photomineralization and transformation of iron oxide nanominerals in aqueous systems. Issue 5 (16th April 2018) - Liu, Lihu; Jia, Zhaoheng; Tan, Wenfeng; Suib, Steven L.; Ge, Le; Qiu, Guohong; Hu, Ronggui
Abstract : Iron oxide nanominerals are generated by photocatalytic oxidation of Fe 2+ aq, and Fe 2+ aq promotes the transformation of the photochemically synthesized schwertmannite. Abstract : The formation and transformation of iron oxide nanominerals in water environments control the migration and conversion of essential and toxic elements and organic pollutants. This study demonstrates the formation of iron oxide nanominerals through the oxidation of Fe 2+ aq by hydroxyl radicals (OH˙) and superoxide radicals (O2 ˙ − ) generated from the photolysis of nitrate. The mineral compositions were affected by the anion species and pH. In the photochemical system, schwertmannite was formed in 5.0 mmol L −1 SO4 2− solution with the initial pH of 6.0, and a mixture of goethite and lepidocrocite was formed when the SO4 2− concentration decreased to 0.1 mmol L −1 . The particle size of schwertmannite increased with decreasing initial pH from 6.0 to 3.0. When Cl − was used instead of SO4 2−, single-phase lepidocrocite was formed with the initial pH of 6.0. When the initial pH decreased to 4.5 and 3.0, a mixture of goethite and lepidocrocite was formed, and the relative content of lepidocrocite decreased with decreasing initial pH. Under anoxic conditions, Fe 2+ aq promoted the transformation of the photochemically synthesized schwertmannite to goethite and lepidocrocite by dissolution–recrystallization. The present work expands our understanding of the generation and transformation of iron oxide nanominerals in nitrate-rich supergene environments.